English at secondary school : perceptions of relevance - Anna Jeeves 1954- (2010)
This study explores the question of perceived relevance of secondary school English studies in Iceland. Little work has been done on the role and nature of relevance in language learning and its relationship to recognized concepts such as motivation, autonomy, self-concept, self-efficacy, and international orientation. The focus is on the experience of students and young people, and on acknowledging the voices of language learners themselves. Through semi-structured interviews, attitudes of secondary school students towards English and English secondary sschool studies are investigated, along with the perceived relevance of these studies to their future identity as English users, and their language needs outside the classroom in the present and the future. In this paper, emerging themes from interviews with secondary school students are discussed and a four-self model of relevance is proposed. Markmið rannsóknarinnar er að kanna viðhorf til gildis enskunáms við íslenska framhaldsskóla. Lítið er vitað um eðli gildis og hvaða hlutverki það gegnir við tileinkun tungumála. Einnig hafa tengsl gildis við þekkt hugtök svo sem hvata, sjálfstæði í námi, sjálfsímynd, og afstöðu til alþjóðasamfélagsins lítið verið rannsökuð. Rannsóknin beinist að upplifun nemenda og ungmenna, og mikilvægi þess að hlusta á raddir málanema. Opin viðtöl eru notuð til að kanna viðhorf framhaldsskólanemenda til ensku og enskunáms. Ennfremur er reynt að komast að gildi enskunámsins og tengingu þess við framtíðarsýn nemenda sem málnotendur, svo og þarfir þeirra hvað varðar tungumálanotkun fyrir utan skólastofuna. Í grein þessari eru kynntar fyrstu niðurstöður úr viðtölum við framhaldsskólanemendur, og lögð drög að „4-sjálfra“ líkani gildisins.